2-Axis controlled spray pyrolysis deposition device for Dye-sensitized Solar Cell (DSSC) - Suriani binti Abu Bakar (Tanjung Malim, 2024)
2-Axis controlled spray pyrolysis deposition device for Dye-sensitized Solar Cell (DSSC) by Suriani binti Abu Bakar